Implication of Organizational Citizenship Behaviour in Nepalese Commercial Banks - Paudel, Sajita; Thapa, Bhupal Krishna; Gurung, Sumer; Lama, Tasi Jangmu (International Journal of Atharva, 2023)
Organizations serve people by working with and for them. Both organizations and their employees are interdependent on each other. Organizational Citizenship Behavior (OCB) plays a vital role in the success of any organization. It encompasses discretionary behaviors exhibited by employees that go beyond their formal job descriptions, contributing to the overall effectiveness and functioning of the organization. This study focused on examining the perspective of employees regarding OCB in the banking industry of Nepal. The study adopted a quantitative research approach through a survey design to sample 40 employees from the banks. With the use of several statistical methods, including means, standard deviations, frequencies, and correlation analysis- data gathered from the questionnaire was analyzed and interpreted, and utilized for the analysis of the research objectives and hypotheses stipulated by the study. The study found that there is no direct proportional relationship between demographic variables and OCB.